Analytical music therapy - Eschen, Johannes Th. (London ; Philadelphia : Jessica Kingsley Publishers, 2002)
This book brings together the professional experiences of eminent analytical music therapists from Europe and the USA. The book examines the origins and theory of AMT (including a contribution on the subject from Mary Priestley), before exploring its uses in various contexts. Chapters cover AMT in counselling and rehabilitation, with adults and children and with nonverbal clients. A concluding section discusses aspects of the training of music therapy students. Written by experienced and highly regarded analytic music therapists, and edited by Johannes Th. Eschen, one of the first ever AMT stu.
Analytical Music Therapy; Contents; Preface; Part 1; 1. Analytical Music Therapy -- Origin and Development; 2. Analytical Music Therapy -- Introduction; 3. Theoretical Bases of Analytical Music Therapy; Part 2; 4. Some Considerations on the Treatment Techniques of Psychoanalytically-Established Music Therapy; 5. Analytical Music Therapy with Adults in Mental Health and in Counselling Work; 6. The Sound of Silence -- The Use of Analytical Music Therapy Techniques with a Nonverbal Client; 7. The Psychodynamic Function of Music in Analytical Music Therapy with Children.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Music therapy -- Methods; Music Therapy -- methods; Musicothérapie -- Méthodes.; Creative Therapy (Eg Art, Music, Drama); MEDICAL -- Allied Health Services -- Occupational Therapy; Music therapy; Musicothérapie.; Methods (Music)